The spirit and the sky : Lakota visions of the cosmos - Hollabaugh, Mark (Studies in the anthropology of North American Indians., 2017)
The interest of nineteenth-century Lakotas in the sun, moon, and stars was an essential part of their never-ending quest to understand the universe. "The Spirit and the Sky" presents a survey of the ethnoastronomy of the nineteenth-century Lakota and relates Lakota astronomy to their cultural practices and beliefs. The center of Lakota belief is the unfathomable and sacred nature of the world in which they live and of the stars above-extraordinary and wakhan (mysterious)-both of which constitute an integral part of this holistic world. Mark Hollabaugh offers a detailed analysis of all aspects of Lakota culture that have a bearing on their astronomy, including telling time, Lakota names for the stars and constellations as they appeared on the Great Plains, and the phenomena of meteor showers, eclipses, and the aurora borealis. Hollabaugh's explanation of the cause of the aurora that occurred at the death of Black Elk in 1950 is a new contribution to ethnoastronomy.